JAPAN AND US: COMPARATIVE ANALYSIS OF NEW APPROACHES TO BILATERAL RELATIONS - V. G. Shvydko; E. A. Klyueva (Сравнительная политика, 2020)
Japan – U.S. relations, which are of great importance for the both countries as well as for international relations in North-East Asia and the Indo-Pacifi c, have experienced signifi cant changes in recent years. While continuing to maintain close military-political alliance with the United States and recognize unconditionally its leadership regarding the choice of strategic course and priorities, Japan is increasingly promoting its own regional policy agenda and its vision of national interests. The main task of its government, headed by Shinzo Abe, is a kind of «rebranding» Japan in political terms as a «normal» country void of negative historical heritage with the ability to employ a full set of foreign policy tools and promote its interests on a regional scale. The said task brings about new accents in Japan’s relations with the USA in the sphere of security, in solving regional political problems and regulating mutual trade and investment. At the same time, bilateral relations are viewed by Japan as a complex set where some elements can be used as a tool or traded as parts of a package deal to secure a comprehensive solution.The United States, for its part, is focusing on maintaining its role as the undisputed leader, trying to neutralize Japan’s attempts to break the framework of the established hierarchical order and change the logic of bilateral relations to that of trading concessions and optimizing complex network balance.Since the change of presidential administration in the US in 2017 there has been a marked decay of long-established consensus on the desirability of further liberalization of international trade and investment through multilateral agreements and frameworks. Like other countries, Japan faced a persistent drive by Trump administration to withdraw from them in favor of bilateral agreements on managed and balanced trade. Japan’s government had to give in to the US pressure and begin negotiations on a bilateral trade agreement designed to reduce imbalance of trade fl ows between the two countries through policy steps to be taken mainly by the Japanese side.